2016
DOI: 10.1002/chem.201602242
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Limonol Derivatives as Heat Shock Protein 90 (Hsp90) Inhibitors through a Multidisciplinary Approach

Abstract: The identification of inhibitors of Hsp90 is currently a primary goal in the development of more effective drugs for the treatment of various types of multidrug resistant malignancies. In an attempt to identify new small molecules modulating the activity of Hsp90, we screened a small library of tetranortriterpenes. A high-affinity interaction with Hsp90 inducible form was uncovered for eight of these compounds, five of which are described here for the first time. By monitoring the ATPase activity and the citra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 65 publications
(145 reference statements)
3
52
0
Order By: Relevance
“…To evaluate the stability of the complexes between JMJD3 and compounds 3 – 12 obtained by docking analysis, we performed molecular dynamics simulations (50 ns, 310 K; see experimental details in the Supporting Information) . The trajectory analysis revealed that 3 gives a high number of contacts with protein residues, and it maintains most of the contacts observed from the docked pose during the entire simulation (>50 %) with both protein models (Figure , bottom).…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the stability of the complexes between JMJD3 and compounds 3 – 12 obtained by docking analysis, we performed molecular dynamics simulations (50 ns, 310 K; see experimental details in the Supporting Information) . The trajectory analysis revealed that 3 gives a high number of contacts with protein residues, and it maintains most of the contacts observed from the docked pose during the entire simulation (>50 %) with both protein models (Figure , bottom).…”
Section: Methodsmentioning
confidence: 99%
“…Among these factors, oxidative stress may cause an imbalance between reactive oxygen species and the anti-oxidant system, which has an important role in the secondary injury component of SCI ( 6 ). Prevention of oxidative stress to reduce the degree of secondary injury has become a potential strategy for the treatment of SCI ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, basing on the data here discussed and already reported by us 25 , 27 , 28 , 41 and by other research groups 45 , 47 49 , we can only suggest the binding location of our molecules on the protein. This region seems to be not completely overlapped both to the allosteric site of Hsp90 (middle:C-terminal domain) 45 , 47 , 48 and to the second nucleotide pocket on Hsp90-C terminus, for which to date, only computational hypothesis can be proposed because its precise physical location in the CTD as well as its exact physiological role are still unclear 49 .…”
Section: Resultsmentioning
confidence: 57%
“… 37 . In order to assess the binding of tested compounds on Hsp90α, we have performed molecular docking experiments using the induced fit docking protocol (Schrödinger Suite) 38 – 40 , to account for flexibility of ligands and receptor 41 . In light of the surface plasmon resonance results and the biological data (see Table S3 , Supplementary Material), we have disclosed two novel not nature-inspired Hsp90 C-terminal inhibitors ( 7 and 10 ).…”
Section: Resultsmentioning
confidence: 99%